(3 x^2 -12 x) + (3 y^2 -30 y) = -84
3( x^2 - 4 x ) + 3 (y^2 -10 y ) =-84
(x^2-4x) + (y^2-10 y) = -28
complete the squares
(x^2-4 x + 4) -4 + (y^2-10 y + 25) -25 = -28
(x-2)^2 + (y-5)^2 = 1 = r^2
got it ?
3x^2+3y^2-12x-30y+84=0 is the equation of a circle with center
(h,k) and radius r
For:
h=
k=
and r=
3 answers
3 x² + 3 y² -12 x - 30 y + 84 = 0
Subtract 84 to both sides
3 x² + 3 y² -12 x - 30 y = - 84
Divide both sides by 3
x² + y² - 4 x - 10 y = - 28
Add 2² + 5² to both sides
( x² - 4 x + 2² ) + ( y² - 10 y + 5² ) = - 28 + 2² + 5²
( x - 2 )² + ( y - 5² ) = - 28 + 4 + 25
( x - 2 )² + ( y - 5² ) = - 28 + 29
( x - 2 )² + ( y - 5² ) = 1
The standard form equation of circle:
( x - h )² + ( y - k )² = r²
h = 2 , k = 5 , r = 1
Subtract 84 to both sides
3 x² + 3 y² -12 x - 30 y = - 84
Divide both sides by 3
x² + y² - 4 x - 10 y = - 28
Add 2² + 5² to both sides
( x² - 4 x + 2² ) + ( y² - 10 y + 5² ) = - 28 + 2² + 5²
( x - 2 )² + ( y - 5² ) = - 28 + 4 + 25
( x - 2 )² + ( y - 5² ) = - 28 + 29
( x - 2 )² + ( y - 5² ) = 1
The standard form equation of circle:
( x - h )² + ( y - k )² = r²
h = 2 , k = 5 , r = 1
My typo:
( x - 2 )² + ( y - 5)² = - 28 + 4 + 25
( x - 2 )² + ( y - 5 )² = - 28 + 29
( x - 2 )² + ( y - 5)² = 1
The same solution as Damon.
( x - 2 )² + ( y - 5)² = - 28 + 4 + 25
( x - 2 )² + ( y - 5 )² = - 28 + 29
( x - 2 )² + ( y - 5)² = 1
The same solution as Damon.